Investigation of combustion and emission characteristics in a TBC diesel engine fuelled with CH4-CO2-H-2 mixtures - YILMAZ, İLKER TURGUT; GÜMÜŞ, METİN (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
In this study, an experimental investigation was performed to reveal combustion and emission characteristics of common-rail four-cylinder diesel engine run with CH4, CO2 and H-2 mixtures. The engine pistons were thermally coated with zirconia and Ni-Al bond coat by plasma spray method. With a small amount of the pilot diesel, port fuelled methane (100% CH4), synthetic biogas (80% CH4 + 20% CO2), and hydrogen presented (80% CH4+10% CO2+10% H-2) mixtures were used as main fuel at different loads (50 Nm, 75 Nm, and 100 Nm) at a constant speed of 1750 min(-1). Comparative analysis of the combustion (cylinder pressure, PRR, HRR, CHR, ringing intensity, CA10, CA50, and CA90), BSFC, and emissions (CO2, HC, NOx, smoke, and oxygen) at the various engine loads with and without piston coating was made for all fuel combinations. It was found that coating the engine pistons enhanced the examining combustion characteristics, whereas it slightly changed BSFC and most of the emissions. As compared to the sole diesel fuel, the gaseous fuel operations showed higher in-cylinder pressure, PRR, and ringing intensity values, earlier combustion starting and CAs, and lower diesel injection pressure at the same engine operating conditions. Dramatic increase in the ringing intensity was particularly found by the hydrogen introduced mixture under the tests with coated piston. HC and CO2 emissions increased in operation with the synthetic biogas; however, hydrogen introduction reduced HC emissions by 4.97-30.92%, and CO2 emissions by 5.16-10%. (C) 2021 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Dual-fuel; Combustion; Emission; Biogas; Hydrogen; Piston coating; INJECTION STRATEGIES; BIODIESEL BLEND; CARBON-DIOXIDE; PERFORMANCE; HYDROGEN; BIOGAS; GAS; ENRICHMENT; PARAMETERS; METHANOL